A novel label-free colorimetric polyA aptasensing approach based on cationic polymer and silver nanoparticles for detection of tobramycin in milk. (15th July 2022) - Mahjub, Reza; Shayesteh, Omid Heydari; Derakhshandeh, Katayoun; Ranjbar, Akram; Mehri, Fereshteh; Heshmati, Ali
Highlights: Introducing the non-thiolated poly-Adenine aptamer, for the first time, as a diagnosis element for determination of tobramycin. Detection limit of 70 pM has been obtained, and tobramycin in the concentration of 1 nM was detected by the naked eye. The aptasensor was rapidly prepared in 10 min, without long immobilization time. The simple, low cost biosensor successfully used for reliable detection of tobramycin in milk sample. Abstract: In this study, a novel colorimetric bioassay method was developed for the sensitive determination of tobramycin (TOB). To detect TOB, silver nanoparticles (AgNPs) were decorated with TOB-specific aptamers (apt), and positively charged poly diallyl dimethyl ammonium chloride (PDDA) was used. As long as tobramycin is not present in the assay system, PDDA can coalesce with the aptamer, and AgNPs would remain stable (λmax = 400 nm) in the dispersed system against PDDA-induced aggregation. When TOB is added, aptamer can bind to the compound, which leads to release of PDDA and subsequent aggregation of AgNPs (λmax = 540 nm). This remarkable change, as a colorimetric analytics signal, can be used for quantitative analysis of TOB. TOB can be detected by this highly sensitive colorimetric aptasensor with a limit of detection (LOD) of 70 pM. Furthermore, TOB can be detected with the naked eye at concentrations above 1 nM.